2017
DOI: 10.1002/marc.201700269
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Folded Single‐Chain Nanoparticle: Nanoclusters and Self‐Assembled Reduction‐Responsive Sub‐5‐nm Discrete Subdomains

Abstract: Easy access to discrete nanoclusters in metal-folded single-chain nanoparticles (metal-SCNPs) and independent ultrafine sudomains in the assemblies via coordination-driven self-assembly of hydrophilic copolymer containing 9% imidazole groups is reported herein. H NMR, dynamic light scattering, and NMR diffusion-ordered spectroscopy results demonstrate self-assembly into metal-SCNPs (>70% imidazole-units folded) by neutralization in the presence of Cu(II) in water to pH 4.6. Further neutralization induces self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…107 In addition, the groups of Rotello and Weck used π-stacking interactions between homo-and heteroaromatic pendants for the reversible folding of copolymers, while O'Reilly and coworkers [108][109][110][111] used ionic interactions. Recently, Artar, 112,113 Cai, [114][115][116] Pomposo, [117][118][119] Lemcoff, [120][121][122] Barner-Kowollik, [123][124][125] Zimmerman, 126 and others have been using a wide variety of metal-ligand complexations to collapse polymer chains. [127][128][129][130][131][132][133] Folding using directional supramolecular motifs in organic media…”
Section: Folding Polymers Via Hydrogen-bond-driven Dimerizationmentioning
confidence: 99%
“…107 In addition, the groups of Rotello and Weck used π-stacking interactions between homo-and heteroaromatic pendants for the reversible folding of copolymers, while O'Reilly and coworkers [108][109][110][111] used ionic interactions. Recently, Artar, 112,113 Cai, [114][115][116] Pomposo, [117][118][119] Lemcoff, [120][121][122] Barner-Kowollik, [123][124][125] Zimmerman, 126 and others have been using a wide variety of metal-ligand complexations to collapse polymer chains. [127][128][129][130][131][132][133] Folding using directional supramolecular motifs in organic media…”
Section: Folding Polymers Via Hydrogen-bond-driven Dimerizationmentioning
confidence: 99%
“…The combination of hydrophobic interactions, metal complexation and electrostatic charges allowed Zimmerman and co-workers to develop a variety of dynamic SCNPs showing enzyme-like catalytic behavior ( Figure 5) [62,63] and, even, able to perform tandem reactions together with enzymes inside living cells [64]. Independently, the presence of compartmentalized ultra-fine nanoclusters in metal folded SCNPs and subdomains in their assemblies was reported by Cai et al [65], which used single chain technology to demonstrate unidirectional cross-domain molecule shutting of dumbbell-shaped SCNPs prepared by stepwise complexation of the outer blocks of an ABC-type linear triblock copolymer to copper ions [66].…”
Section: Multi-folded Single-chain Nanoparticles Via Non-covalent Bondsmentioning
confidence: 78%
“…HisMA monomer was obtained via the reaction of histamine with methacryloyl chloride. , 1 H NMR and 13 C NMR spectra suggest high purity (Figure S1). The diblock copolymer macro-CTA was synthesized via visible light-initiated RAFT aqueous solution polymerization. , 1 H NMR and SEC studies indicated well-defined CTA-1 (A 39 B 41 -TTC, Figure S2) and CTA-2 (B 43 A 38 -TTC, Figure S3) with the high fidelities of RAFT end groups.…”
Section: Resultsmentioning
confidence: 99%